Mapping brain Fos immunoreactivity in response to water deprivation and partial rehydration: influence of sodium intake - Dalmasso, Carolina; Antunes-Rodrigues, José; Vivas, Laura; De Luca, Laurival A. [UNESP] (Elsevier B. V., 2015)
Water deprivation (WD) followed by water intake to satiety, produces satiation of thirst and partial rehydration (PR). Thus, WD-PR is a natural method to differentiate thirst from sodium appetite. WD-PR also produces Fos immunoreactivity (Fos-ir) in interconnected areas of a brain circuit postulated to subserve sodium appetite. In the present work, we evaluated the effect of sodium intake on Fos-ir produced by WD-PR in brain areas operationally defined according to the literature as either facilitatory or inhibitory to sodium intake. Isotonic NaCl was available for ingestion in a sodium appetite test performed immediately after a single episode of WD-PR. Sodium intake decreased Fos-ir in facilitatory areas such as the lamina terminalis (particularly subfornical organ and median preoptic nucleus), central amygdala and hypothalamic parvocellular paraventricular nucleus in the forebrain. Sodium intake also decreased Fos-ir in inhibitory areas such as the area postrema, lateral parabrachial nucleus and nucleus of the solitary tract in the hindbrain. In contrast, sodium intake further increased Fos-ir that was activated by water deprivation in the dorsal raphe nucleus, another inhibitory area localized in the hindbrain. WD-PR increased Fos-ir in the core and shell of the nucleus accumbens. Sodium intake reduced Fos-ir in both parts of the accumbens. In summary, sodium intake following WD-PR reduced Fos-ir in most facilitatory and inhibitory areas, but increased Fos-ir in another inhibitory area. It also reduced Fos-ir in a reward area (accumbens). The results suggest a functional link between sodium intake and the activity of the hindbrain-forebrain circuitry subserving reward and sodium appetite in response to water deprivation.
Keywords: Angiotensin ii; Reward; Satiety; Sodium appetite; Thirst; Water intake